Approaches to workload in psychiatric and mental health nursing - Tássia Ghissoni Pedroso; Luiz Jorge Pedrão; Marcia Galan Perroca (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to investigate approaches to workload in psychiatric and mental health nursing in Brazilian and international production of knowledge Methods: integrative literature review using six databases, covering January 2005 to March 2019. Articles in full in English, Spanish and Portuguese were included. Results: the sample consisted of 23 original articles classified as quantitative or emotional. The quantitative dimension was addressed in 12 articles and included: assessing patient care needs, identifying activities performed by the team, measuring time spent and developing and validating a measurement instrument. The emotional dimension included 11 articles the focus of which was on identifying stressors in the workplace, psychosocial risks and coping strategies. Conclusion: strategies were found for measuring workload and assessing the impact of stressors on nursing teams.